PENGARUH STORE ATMOSPHERE, BRAND IMAGE, DAN CUSTOMER PERCEIVED VALUE TERHADAP PURCHASE INTENTION GENERASI Z PADA WARUNG RAKYAT MOJOKERTO - Hanafi, Whildan Ali; Andayani, Sri; Mulyati, Diana Juni (Research Journal of Social Science and Economics, 2025)
This study aims to determine the effect of store atmosphere, brand image, and customer perceived value on the purchase intention of generation Z at Warung Rakyat in Mojokerto. This study uses a quantitative method with a data collection approach that is carried out through online questionnaires to 100 generation Z respondents who are customers of Warung Rakyat Mojokerto. The results of data analysis using the multiple linear regression method show that store atmosphere, brand image, and customer perceived value positively and significantly influence generation Z purchase intention at Warung Rakyat Mojokerto. The findings of this study indicate that the factors of the store environment, brand image, and customer perceptions of the value they receive greatly influence the purchase intention of Generation Z at Warung Rakyat. This research has important implications for Warung Rakyat Mojokerto owners in improving their marketing strategy. By paying attention to and improving the store atmosphere, building a strong brand image, and providing better value to customers, Warung Rakyat owners can increase Gen Z’s purchase intentions and expand their market share.